Advanced Fuzzy Logic Control application for Tracking Inverted Pendulum Sana Iqbal1, Mohammad Ayyub2, Mohammad Sarfraz3 - Sana Iqbal, Mohammad Ayyub, Mohammad Sarfraz (International Journal of Advanced Science and Technology, 2020)
In this work, we have implemented different fuzzy controllers to have a good steady-state as well as transient response. When the controlled system’s parameters undergo a change that may be due to change in the system parameters or due to external disturbance, in such a way that they cannot be predicted from the very beginning, the design method cannot assure the closed-loop system’s stability, so this is the platform where adaptive control approach seems to be most prominent and active. A fuzzy model has an outstanding characteristics to simplify  an intricate and unpredictable system and is predominantly appropriate for modeling of nonlinear systems. Therefore, the adaptive control approach delivers an exciting alternative when there are significant numbers of fuzzy local models. The main advantage is that it simplifies the global stability analysis, and with limited modeling effort, a model structure can be found frequently. The combination of the benefits of two control methods and then the implementation of a proposed novel stabilizing controller will, therefore, have preferred output over that based on single control theory.